Cross sectional evidence on the relation between monetary policy, macroeconomic conditions and low-frequency inflation uncertainty: conference paper - Conrad, Christian; Hartmann, Matthias (Jahrestagung des Vereins für Socialpolitik 2014, 2014)
In this study, we examine how the interaction between monetary policy and macroeconomic conditions affects inflation uncertainty in the long-term. The unobservable inflation uncertainty is quantified by means of the slowly evolving unconditional variance component of inflation in the framework of the semiparametric Spline-GARCH model (Engle and Rangel, 2008). For a cross section of 13 developed economies, we find that long-term inflation uncertainty is high if central bank governors are perceived as less inflation-averse, if the conduct of monetary policy is rather ad-hoc than rule-based and in economies with a low degree of central bank independence.